Deep Gaussian process with uncertainty estimation for microsatellite instability and immunotherapy response prediction from histology - Sunho Park; Morgan F. Pettigrew; Yoon Jin Cha; In-Ho Kim; Minji Kim; Imon Banerjee; Isabel Barnfather; Jean R. Clemenceau; Inyeop Jang; Hyunki Kim; Younghoon Kim; Rish K. Pai; et al. (npj Digital Medicine)
Abstract Determining tumor microsatellite status has significant clinical value because tumors that are microsatellite instability-high (MSI-H) or mismatch repair deficient (dMMR) respond well to immune checkpoint inhibitors (ICIs) and oftentimes not to chemotherapeutics. We propose MSI-SEER, a deep Gaussian process-based Bayesian model that analyzes H&E whole-slide images in weakly-supervised-learning to predict microsatellite status in gastric and colorectal cancers. We performed extensive validation using multiple large datasets comprised of patients from diverse racial backgrounds. MSI-SEER achieved state-of-the-art performance with MSI prediction by integrating uncertainty prediction. We achieved high accuracy for predicting ICI responsiveness by combining tumor MSI status with stroma-to-tumor ratio. Finally, MSI-SEER’s tile-level predictions revealed novel insights into the role of spatial distribution of MSI-H regions in the tumor microenvironment and ICI response.